The Factors Affecting Poverty in Malaysia: Macroeconomic Perspectives - Norasikin, Nur Nadhirah Khaleeda; Azhar, Nur Azirah Zahida Azhar Mohamad (Advances in Social Sciences Research Journal, 2024)
The poverty issue is important because it is the first goal of the SDG in Malaysia. Since income level is not a reliable indication of poverty because it does not consider someone to be living in poverty if their income is below the poverty line. Based on previous literature, the researcher recognises the deficiency. Due to a lack of data and studies from earlier studies and literature reviews in Malaysia, it is still unclear how inflation, unemployment, and economic growth are affected by poverty. Therefore, this paper provides the conceptual review on how the macroeconomic factors affect the poverty incidence in Malaysia. However, the study examines the association between poverty which inflation, unemployment and economic growth using multiple regression estimators. Results show that inflation, unemployment and economic growth has a positive significant relationship with poverty incidence in Malaysia.